A Pengembangan Program Kesehatan Mental Remaja Berbasis Teknologi Pada Remaja Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2025: Development of a Technology-Based Mental Health Program for Adolescents in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province in 2025 - Simanjuntak, Parningotan; Nopalina Suyanti Damanik; Nur Azizah; Siska Suci Triana Ginting; Roy Saputra Berutu (Jurnal Pengabdian, 2025)
Data from the Indonesian Ministry of Health (2023) shows that around 15.6% of adolescents in Indonesia experience symptoms of mental health disorders, but most do not receive adequate treatment. In North Sumatra, the rate of emotional mental disorders in adolescents is also relatively high, influenced by urbanization, promiscuity, and lack of access to youth-friendly counseling services. This community service activity uses a participatory and collaborative approach by involving adolescents, village officials, schools, community health centers, and psychology experts. Location: Bangun Rejo Village Hall & the digital platform developed with the target activity being adolescents aged 13–19 years who live in Bangun Rejo Village, with a target of at least 50 active participants. Target criteria include: Adolescents who have a device (smartphone) and internet access, Willing to participate in all series of activities, Obtaining permission from parents/guardians to participate in the program. The approach is carried out in three stages: Preparation (Initial survey of adolescent mental health conditions, Development of educational modules and materials, Formation of an implementation team), Program Implementation (Face-to-Face Education, Peer Counselor Training, Digital Platform Development, Online Counseling), Evaluation (Pre-test and Post-test, Evaluation of participant engagement, Short interviews). Activity Results: The Technology-Based Youth Mental Health Program Development Program in Bangun Rejo Village was implemented from February to April 2025, with the following results: Initial participants (registration): 50 adolescents, Active participants until the end of the program: 48 adolescents (96%), Average attendance per face-to-face session: 92%. It is hoped that participants will continue to utilize the established digital platform and peer counselors to support each other in maintaining mental health